La composition architecturale de l’Hécube d’Euripide - Irigoin, J. (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2002)
A simple test, counting the iambic trimeters in the spoken segments of Hecuba, shows that Euripides, before embarking on the actual text, draws a chart where the exact number of verses in every unit of the tragedy is found. We can see the tragedy split into two mirroring halves of 456 (2x12x19) trimeters: the thickening of the plot (desis) and its unwinding (lusis), as defined by Aristotle in the chapter 12 of the Poetics. Such kind of numerical composition, already practised by Aeschylus and continued by Sophocles, has been meticulously preserved in the byzantine manuscripts of the three tragedians. Therefore the editors must preserve, excepting counted occasions, the numerus versuum of the tradition, in order to keep the equation as it was set by the poet.
Keywords: Greek tragedy; Euripides; Hecuba; iambic trimeter; numerical composition; textual criticism